School Principals and Students with Special Education Needs: Leading Inclusive Schools - Sider, Steve; Maich, Kimberly; Morvan, Jhonel (Canadian Journal of Education/Revue canadienne de l’éducation, 2017)
Over the past 30 years, school boards, faculties of education, and teaching organizations have helped teachers develop skills to support students with special education needs in their classrooms. However, less attention has been given to school principals in building their leadership skills to support inclusive schools. The purpose of this study is to identify the types of special education training that school principals engage in, as well as to explore the day-to-day issues and critical incidents that principals might experience when supporting students with special education needs. An exploratory study involving interviews with 15 principals and five other educational stakeholders in four school boards was employed to examine the related research questions. Five key themes emerged from the analysis of the interviews, including personal values in shaping inclusive school culture; variety in professional learning experiences; similarities in day-to-day experiences and the importance of being accessible for students and staff; the importance of leadership in fostering inclusive school culture; and the effect of critical incidents in shaping principals’ leadership roles. These themes are examined in light of the literature contending that school leaders are central to the shaping of inclusive school cultures.